Embodying decolonial democracy: The teachers' union and the People's Guelaguetza in Oaxaca, Mexico. (29th January 2019) - Affourtit, Lorraine
Abstract : The annual strike encampment staged by Local Section 22 of the National Union of Education Workers ( Sindicato Nacional de Trabajadores de la Educación [SNTE]) in Oaxaca, Mexico was violently repressed in the summer of 2006, resulting in a massive uprising led by the newly formed Popular Assembly of the Peoples of Oaxaca (APPO). APPO and Section 22 created the People's Guelaguetza indigenous folk festival as an alternative to the state's Guelaguetza, which had become a commercialized spectacle aimed at generating tourist revenue. I analyze the People's Guelaguetza as a union strategy both in the context of Oaxaca's 2006 uprising and in the festival's continuing yearly iteration. I contend that the People's Guelaguetza provides a hybrid cultural‐political forum mobilizing a two‐pronged approach to support short‐ and long‐term union goals, first to denounce a threat imposed from above and then to promote an alternative innovated from below. In 2006, the festival denounced the state and prefigured, through visual and embodied modes of indigenous self‐representation, APPO's participatory democratic model of political engagement based in indigenous communal lifeways. In its post‐APPO iteration, the People's Guelaguetza opposes neoliberal government education reforms and endorses union‐generated educational initiatives addressing the needs of Oaxaca's indigenous rural poor.